What Socrates drank? Comparative chemical investigation of two Greek Conium taxa exhibiting diverse chemical profiles. (March 2022) - Vlassi, Anthi; Koutsaviti, Aikaterini; Constantinidis, Theophanis; Ioannou, Efstathia; Tzakou, Olga
Abstract: Conium divaricatum, even though exhibiting morphological differences in comparison to its congener of European origin Conium maculatum, is still considered a disputed taxon often referred to as a synonym of the latter. Herein, essential oils of various plant tissues from several populations of both taxa were comparatively investigated, showing distinct chemical profiles. In the case of C. divaricatum, the essential oils were dominated by hydrocarbon esters, among which the main constituents 4′-oxodecyl hexanoate, 4′-oxododecyl hexanoate and 4′-oxooctyl hexanoate were isolated and identified as undescribed natural products. In contrast, the essential oils of C. maculatum were dominated by hydrocarbon alkanes, alkenes and ketones, as well as the polyacetylene ( Z )-falcarinol. Even though determination of the total alkaloids content and toxicity assessment against the crustacean Artemia salina did not reveal significant differences, the distinct chemical profiles and the morphological differences observed for both taxa, strongly support their distinction as separate species. Graphical abstract: Image 1 Highlights: Conium divaricatum and Conium maculatum essential oils were comparatively studied. The two taxa displayed distinct chemical profiles. Three undescribed metabolites were isolated and identified from C. divaricatum. The total alkaloids content and the toxicity against brine shrimp were evaluated. These data strongly support the distinction of the two taxa as separate species.